FACTORS THAT AFFECT THE CAPITAL STRUCUTRE IN REAL ESTATE AND PROPERTY COMPANIES IN INDONESIAN STOCK EXCHANGE - Kharisma Devi Pratiwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Capital structure is an important issue for any companies; good or bad capital structure will have a direct effect on the financial position of the company. The problems being faced by the real estate and property companies that go public on the Stock Exchange is the high level of debt held. With the high levels of debt caused a decline in value of the company in the eyes of the investors. The existence of this phenomenon, there is an interest to learn about the effect of simultaneous, effect of partial and variable dominant: asset structure, profitability, company size and sales growth in the capital structure of real estate and property companies that went public on the Stock Exchange. The population of this study is all real estate and property companies listed in the Stock Exchange in 2013, amounting to 17 companies. Sampling was done by purposive sampling method with the criteria that the real estate and property companies are actively listed on the Stock Exchange and included summary financial statements are recorded in the Indonesian Capital Market Directory, for the period 2009-2011. Based on the criteria selected as the study sample as many as 13 companies. Asset structure, profitability, company size, sales growth, simultaneously, and partially has significant impact on capital structure. Firm size has a dominant influence on the capital structure of the Company Property and Real estate in Indonesia Stock Exchange. The financial manager should consider, the financing of the assets arrangement is useful for achieving the level of profit from the sale are expected, and in accordance with the size of the company. In addition to the need to consider the use of debt careful, because if additional debt is too large can reduce a company's financial performance. Stability sales growth rate must be considered, so as to contribute to profitability. Keyword: Assets Structure, Profitability, Company Size, Sales Growth, Capital Structure